Research at a Distance: Replicating Semantic Differentiation Effects Using Remote Data Collection With Children Participants - Vales, Catarina; Wu, Christine; Torrance, Jennifer; Shannon, Heather; States, Sarah L.; Fisher, Anna V. (Frontiers in Psychology, 2021)
Remote data collection procedures can strengthen developmental science by addressing current limitations to in-person data collection and helping recruit more diverse and larger samples of participants. Thus, remote data collection opens an opportunity for more equitable and more replicable developmental science. However, it remains an open question whether remote data collection procedures with children participants produce results comparable to those obtained using in-person data collection. This knowledge is critical to integrate results across studies using different data collection procedures. We developed novel web-based versions of two tasks that have been used in prior work with 4-6 year-old children and recruited children who were participating in a virtual enrichment program. We report the first successful remote replication of two key experimental effects that speak to the emergence of structured semantic representations (N=52) and their role in inferential reasoning (N=40). We discuss the implications of these findings for using remote data collection with children participants, for maintaining research collaborations with community settings, and for strengthening methodological practices in developmental science.